PROFIL BERPIKIR KRITIS DALAM PEMECAHAN MASALAH SOAL CERITA MATEMATIKA DITINJAU DARI GAYA KOGNITIF SISWA - Yohana Eka Kusuma Dewi; Sutriyono ,; Fika Widya Pratama (Universitas Muhammadiyah Semarang, 2019)
The purposes of this research is elaborating the capability of thinking critically FRISCO (Focus, Reason, Inference, Situation, Clarity and Overview) in solving problem based on Polya stage (Research is underdtanding the problems, Creating the plan, Implementing the plan and Reviewing), as reviewd by cognitive style of Field Dependent (FD) and Field Independent (FI). It is such a kind of qualitative descriptive and purposive technical sampling research used in this thesis, after some experiments the author found 1 particular subject in each style wether it from Field Dependent (FD) style of Field Independent (FI) style which was taken from Christian 2 junior high school Salatiga. Based on the research, FD subject incapable of implementing Polya stage, while FI subject capable of implementing Polya stage. Based on those four stages: FD is lack of capabillities compliying the criteria of FRISCO, while FI subject meets the requirements of FRISCO.